The expression of ghrelin, Hsp70, Bcl-2 and bax proteins In idiopathic thrombocytopenic purpura at bone marrow - Cay, Mevra Yasar; Akarsu, Saadet; Ozercan, Ibrahim Hanifi (Wiley-Blackwell, 2016)
[Abstract Not Available]